Comparison of efficiency between two artificial insemination methods using fresh semen in domestic cat (Felis Catus) (Revista de Ciências Agroveterinárias, 2023)
The objective of this study was to compare pregnancy rates in domestic cats using fresh semen for the bilateral intrauterine insemination (BIUI) method and the novel uterine body insemination (UBI) method. Queens received a single injection of equine chorionic gonadotropin (eCG) (200 IU; IM) to induce ovarian follicular development and, after 83 h, an injection of human chorionic gonadotropin (hCG) (100 IU; IM) for final oocyte maturation and ovulation induction. Thirty-four hours after hCG administration, 3 × 106 fresh spermatozoa were used for insemination by the BIUI (n = 8 queens) or by the UBI (n = 7 queens) techniques respectively. Pregnancy rates were 75.00% (6/8) by BIUI and 42.85% (3/7) by the UBI method. The mean litter size was 3.0 ± 0.86 for the BIUI, and 2.0 ± 1.0 for the UBI method. Spontaneous abortion occurred on day 35 of pregnancy in one queen following the UBI method. Our findings showed that the BIUI of queens with fresh semen resulted in higher pregnancy rates than the novel UBI method; also, acceptable pregnancy rates were achieved following BIUI with fresh semen in the domestic cat.
Keywords: intrauterine insemination; fresh semen; insemination; reproductive techniques, assisted; cats